2005
DOI: 10.7773/cm.v31i2.61
|View full text |Cite
|
Sign up to set email alerts
|

Weaning of Senegalese sole (Solea senegalensis) postlarvae to an inert diet with a co-feeding regime

Abstract: The objective of this study was to evaluate the weaning success of Senegalese sole, Solea senegalensis, postlarvae when cofed a compound diet, by means of the analysis of growth parameters (relative growth rate [RGR] and condition factor [K]), survival, protein and lipid content. Total ammonia in the rearing water was also measured. The experiment lasted for 46 days (36 to 82 days posthatching). One group was fed only with enriched Artemia sp. metanauplii (Artemia treatment), whereas in another group, the Arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(67 reference statements)
1
3
0
2
Order By: Relevance
“…(Hamza et al 2008). The obtained results in the present study are relatively in agreement with those obtained by Ribeiro, et al (2005). They evaluated the weaning success of Solea senegalensis larvae.…”
Section: Larval Length and Length Gainsupporting
confidence: 91%
See 1 more Smart Citation
“…(Hamza et al 2008). The obtained results in the present study are relatively in agreement with those obtained by Ribeiro, et al (2005). They evaluated the weaning success of Solea senegalensis larvae.…”
Section: Larval Length and Length Gainsupporting
confidence: 91%
“…The obtained results indicated that the late weaning of larvae (60 dph) significantly (P<0.05) increased each of protein and fat content of larvae when compared to the early weaning (35 dph). For the same trend, Ribeiro, et al (2005) found that, Senegalese sole Solea senegalensis post larvae fed a compound diet adapted to the diet at the end of the experiment, but post larvae from the artemia treatment exhibited significantly (P<0.05) higher values for protein and total lipid contents.…”
Section: Specific Growth Rate (Sgr) Of Length Of Gilthead Seabream Lamentioning
confidence: 56%
“…The early weaning of 15 dph larvae after natural zooplankton feeding has not yet been tested in this species. Nevertheless, this possibility has been tested successfully in marine species like Red porgy ( Pagrus pagrus ), with a weaning protocol (co‐feeding) involving live prey and dry diets (Aristizábal & Suárez 2006), or Sole ( S. senegalensis ) (Ribeiro, Engrola & Dinis 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Modern day aquaculture, requiring intensive production of fish, depends on successful intensive hatchery rearing of larva and juveniles. For sole, larval rearing and weaning in captivity, the two main obstacles for a successful aquaculture rearing of this species, have been overcome successfully (Cañavate & Fernández‐Díaz 1999; Dinis et al 1999; Engrola, Conceição, Gavaia, Cancela & Dinis 2005; Ribeiro, Engrola & Dinis 2005; Engrola, Conceição, Dias, Pereira, Ribeiro & Dinis 2007). This species is now achieving good survival rates at early stages and good growth performance in intensive systems, with results similar to other marine fish already established in commercial aquaculture (Conceição et al 2007).…”
Section: Introductionmentioning
confidence: 99%